The Wept of Wish-Ton-Wish - Cooper, James Fenimore, 1789-1851 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Wept of Wish-Ton-Wish" by James Fenimore Cooper is a historical novel published in 1829. Set during the brutal King Philip's War, it follows Captain Mark Heathcote, a Puritan militiaman who carves out a settlement in the Connecticut wilderness. His family faces constant conflict with Native Americans, including a captured Narragansett youth named Conanchet. Years later, a shocking family reunion reveals the devastating human cost of frontier violence and cultural collision in colonial America. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Wept_of_Wish-ton-Wish
Release date is 2005-09-01
Produced by Project Gutenberg Distributed Proofreaders
Keywords: Historical fiction; War stories; King Philip's War, 1675-1676 -- Fiction